2021
DOI: 10.1016/j.sjbs.2021.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Seed germination with titanium dioxide nanoparticles enhances water supply, reserve mobilization, oxidative stress and antioxidant enzyme activities in pea

Abstract: The nanoparticle has been reported to have severe effects and metabolic disorders in crops. Analysis of poisoning exposure to titanium dioxide is very important during the seed germination stage. Measuring the levels of water supply, reserve mobilization and redox metabolism with germination success is a prerequisite for understanding the TiO 2 stress mechanism. These measurements are carried out using different methods, including germination tests, determination of growth parameters, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In chickpea seeds, the SNP application caused the genetic expression of α-amylase 750 times (Pandey et al, 2019). Basahi (2021) states that oxidative and metabolic disorders are among the main causes of the successful germination of pea seeds. Based on this information, one can verify the direct relationships between higher germination and vigor (Figure 1), higher enzymatic activity (Figure 2), lower contents of H 2 O 2 and O 2 •and MDA (Figure 3) and higher activity of amylases (Figure 4) observed in seeds submitted to -0.15 MPa + SNP treatment when compared to water deficit (-0.15 MPa).…”
Section: Resultsmentioning
confidence: 99%
“…In chickpea seeds, the SNP application caused the genetic expression of α-amylase 750 times (Pandey et al, 2019). Basahi (2021) states that oxidative and metabolic disorders are among the main causes of the successful germination of pea seeds. Based on this information, one can verify the direct relationships between higher germination and vigor (Figure 1), higher enzymatic activity (Figure 2), lower contents of H 2 O 2 and O 2 •and MDA (Figure 3) and higher activity of amylases (Figure 4) observed in seeds submitted to -0.15 MPa + SNP treatment when compared to water deficit (-0.15 MPa).…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation for this might be that GPX is ubiquitous haem-containing enzyme participating in many physiological processes such as ROS scavenging. Some authors have speculated that nanoparticles treatments triggered the accumulation of reactive oxygen species, increased production of stress enzymes that ultimately lead to a better and more stable redox status (Basahi, 2021). Despite the stimulation of the antioxidant system in the rapeseeds plants initiated by nanoparticles spray, it appears that there was a significant lipid peroxidation activity and MDA production especially in Alonso variety.…”
Section: Resultsmentioning
confidence: 99%
“…TiO2 nanoparticles are also used as an essential nutrient for plant growth and development and also improves the photosynthetic pigments in plants such as chlorophylls, carotenoids and anthocyanins contents, therefore, enhanced the crop growth and yield (Chaudhary and Singh, 2020). Modern management of companies, regardless of the activity in which the company operates, requires top management to apply and introduce internal control mechanisms (Popović et al, 2020c;2021). Despite the plenty of information available on foliar application of some nanoparticles on plant growth and development, there is no sufficient information about efficiency of Si and Ti nanoparticles under natural farm conditions in semi-arid regions where water scarcity and high temperature have negative impacts on plants.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…In comparison to other treatments, the combined input of NMs demonstrated greater plant growth, physiological responses, transpiration rate, endogenous elements, and the lowest levels of leaf abscisic acid [99]. In another study, the effects of seed priming with various doses of TiO 2 NMs (40, 60, and 80 ppm) were analyzed on the germination, growth, and physiological implications in Z. mays under salinity stress [100]. The result demonstrated that priming TiO 2 NMs at 60 ppm had beneficial effects on Z. mays seedling development and germination under salt stress.…”
Section: Salinity Stressmentioning
confidence: 99%